Designing an Integrated Assessment System for Critical Thinking in the Field of Literary Studies - Ledesma Urruti, Vanesa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper addresses the need for innovation in Critical Thinking assessment methods. In order to account for the diversity and interdisciplinarity of critical, argumentative and discursive competences in the field of literary studies, an Integrated Assessment System has been designed. This integrated system has helped innovative university professors create different assessment tools including rubrics both for oral and written tasks, self-evaluation questionnaires, peer evaluation sheets, and checklists, all of which are interrelated following assessment standard, key competence and minimum requirement criteria.